CRITICAL DISCOURSE ANALYSIS: DONALD TRUMP SPEECH BROUGHT THE U.S. TO PANDEMIC PREVENTION FAILURE - Arif, Lalu Mochamad; Muhid, Abdul; Hastuti, Hilda (ETNOLINGUAL, 2023)
This research focuses on Donald trump's speech on preventing COVID-19 at White House Conference on May 18, 2020. His speech was about the suggestion on taking hydroxychloroquine which known as an anti-malaria. The method used in this research is mix method, as the data displayed using description and numbers and the analysis data of this research uses critical discourse theory by Fairclough, and meta function within systematic functional linguistic proposed as the tool to scrutinized the object of the research through transitivity analysis, modality analysis, and textual analysis. As for the result of the research shown that (1)the most process used by trump is material process; (2)mental process, in which becomes the reason of the audience has unconsciously followed the irresponsible suggestion by Trump; (3)modality analysis shows that Trump rarely used modal verb; (4) textual analysis shows that Donald Trump's speech has been delivered coherently and transitivity analysis found two the new process forms, both processes are existential process + relational process and relational process + existential process.